(untitled) (International Conference on Computing, Artificial Intelligence and Information Systems, 2026)
In the current context of the formation of a multi-polar global system and the re-distribution of power in favor of the Asia-Pacific region, tensions are increasing in various parts of the world. The South China Sea stands out as one of the most disputed areas due to overlapping interests of various nations. If we talk about China’s actions in the South China Sea and in general about the essence of this problem, we must first of all focus on why this area is of such importance at all, attracts such forces, why the parties involved in the disputes around the South China Sea are ready to go to a rather harsh political confrontation over this area. The conflict is primarily strategic and is not driven by any significant resource competition, even though the South China Sea possesses considerable oil and gas reserves.